2021
DOI: 10.1007/s00216-020-03124-3
|View full text |Cite
|
Sign up to set email alerts
|

Selection and applications of functional nucleic acids for infectious disease detection and prevention

Abstract: Infectious diseases caused by pathogenic microorganisms such as viruses and bacteria pose a great threat to human health. Although a significant progress has been obtained in the diagnosis and prevention of infectious diseases, it still remains challenging to develop rapid and cost-effective detection approaches and overcome the side effects of therapeutic agents and pathogen resistance. Functional nucleic acids (FNAs), especially the most widely used aptamers and DNAzymes, hold the advantages of high stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 147 publications
(191 reference statements)
0
10
0
Order By: Relevance
“…However, in the turbulent situation of global epidemic, domestic epidemic prevention and control still face the pressure of external prevention of importation and internal prevention of rebound, and it is imperative to strengthen the construction of fever clinics and comprehensive control of nosocomial infections. Research reports on fever clinics in China in recent years have shown that the construction of fever clinics across the country is severely weakened or even virtual, revealing many problems in the prevention and control of infectious diseases [ 7 , 8 ]. The reasons for this situation are the lack of a reasonable disciplinary orientation of the fever clinic, the irregularity of the medical and nursing staff, the lack of ability of the medical and nursing staff to screen and handle febrile diseases, and the lack of identification, prevention, and control of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the turbulent situation of global epidemic, domestic epidemic prevention and control still face the pressure of external prevention of importation and internal prevention of rebound, and it is imperative to strengthen the construction of fever clinics and comprehensive control of nosocomial infections. Research reports on fever clinics in China in recent years have shown that the construction of fever clinics across the country is severely weakened or even virtual, revealing many problems in the prevention and control of infectious diseases [ 7 , 8 ]. The reasons for this situation are the lack of a reasonable disciplinary orientation of the fever clinic, the irregularity of the medical and nursing staff, the lack of ability of the medical and nursing staff to screen and handle febrile diseases, and the lack of identification, prevention, and control of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…DNAzymes consist of ssDNA molecules from a random DNA library selected in vitro and distinguished from aptamers by the addition of catalytic activity ( Zhu et al, 2021 ). Among these, the commonly available are RNA-cleaved DNAzymes and G-quadruplex DNAzymes.…”
Section: In Vitro Selection Of Functional Nucleic Acids Towards Understanding Covid-19mentioning
confidence: 99%
“…Meanwhile, functional nucleic acids (FNAs) were discovered via in vitro selection with significant concern are of primary concern within the biological and medical communities owing of the distinctive properties of their target recognition and catalysis ( Zhang et al, 2019 ). FNAs possess the following advantages: lower molecular weight and better permeability of FNAs make in vivo applications more possible; it is easy and inexpensive to modify FNAs, which can be produced in large quantities, by solid-phase synthesis; FNAs play a role in immune-related assays due to their lower immunospecificity than antibodies; the library contains a large number of random sequences, and different FNAs for a target can be endowed with a wealth of functionalities ( Zhu et al, 2021 ). FNAs are currently employed for the detection and therapeutic purposes of diseases caused by pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is a surrogate marker for the specific protein to be detected and contains a specific molecular barcode. Circularized padlock probes are amplified directly by either polymerase chain reaction (PCR) or rolling circle amplification (RCA) processes, taking advantage of SybrGreen real-time PCR amplification monitoring techniques for target detection ( 86 ). The PLA assays have been used to detect porcine parvovirus and foot-and-mouth disease virus ( 87 ).…”
Section: Molecular Assaysmentioning
confidence: 99%